Usaha Mikro Pembuat Krupuk Mbothe, Emping Belinjo dan Krupuk Puli Sehat Desa Kedungsalam Kecamatan Donomulyo Kabupaten Malang - Sri Indrawati; Triana Murtiningtyas (Jurnal ABM Mengabdi, 2016)
Both partners are producing belinjo chips, crackers and chips pulleys mbothe healthy without borax. Raw materials that were encountered in the community rather than sell as raw material because it will give them more profits. The process used in production partners was very simple tools so produced little production capacity and partners can not reach all demands, especially during religious holidays. Likewise tool used for packing still use candles. Regional marketing of these products already covers almost all the areas in East Java. This is supported by the dean partner location with the beach resort Ngliyep. Management of the business partners using simple management pattern, since no complete records pertaining to the entry and exit of money in the production process so that unknown net profit gained real partners. The author hopes that this IbM program impact the development of micro-enterprises is that it can create greater employment for the local population in order to reduce poverty that many encounter in the area.